Management of acute cholecystitis in patient with cyclic neutropenia: a case report - Saki Nishikawa; Michinori Hamaoka; Hideki Nakahara; Toshiyuki Itamoto (Surgical Case Reports, 2021)
Abstract Background Cyclic neutropenia is a disease that causes a neutropenic decrease in peripheral blood in a cycle of about 21 days. It is a rare hereditary disorder with an estimated incidence of 0.5–1 cases per million population. The absolute neutrophil count can drop to zero, and neutropenic nadir may last for 3–5 days. This is a rare disease, and there are few reports of abdominal surgery in cyclic neutropenia patients; thus, we report this case of neutrophil count fluctuation and perioperative management. Case presentation A 31-year-old man with cyclic neutropenia was transferred to our hospital complaining of right season rib pain, but no rebound tenderness. His C-reactive protein was elevated (4.37 mg/L) and computed tomography revealed a large number of small stones in the gallbladder body and an incarceration in the gallbladder neck. He was diagnosed with acute cholecystitis. Ideally, surgical intervention should have been performed immediately, but because his neutrophil count was 300/μL, endoscopic naso-gallbladder drainage was performed and he was provided antibiotics until his neutrophil count increased to acceptable levels. Three days after admission, his neutrophil count had increased and laparoscopic cholecystectomy was performed. For one week after the operation, antibiotics were administered; he had an uneventful postoperative recovery. He was discharged on the seventh postoperative day and provided an oral antibiotic. Conclusions Infection can be serious in patients with cyclic neutropenia, and it is therefore, important to determine the timing of surgery and to apply appropriate perioperative management with drainage and antibiotic administration.